2011
DOI: 10.1063/1.3600328
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-mode excitation in spin-transfer nanocontacts with dynamic polarizer

Abstract: We report our study on the emission response of a magnetic nanocontact with dynamic polarizer in perpendicular magnetic field. In this configuration three modes are accessible, two of which correspond to the precessional motion of a vortex in one of the two ferromagnetic layers with the other working as a static polarizer. At high currents a third mode can be observed that is ascribed to the simultaneous precession of two vortices, one in each layer, with the other layer working as a dynamic polarizer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
7
2
Order By: Relevance
“…21,22 Especially, vortices that are coupled vertically via a nonmagnetic interlayer are of interest, [23][24][25][26][27][28][29][30][31][32][33][34] as significant magnetoresistance and spin-torque phenomena may occur. [35][36][37][38][39] The relevant coupling mechanisms for such geometries are the magnetodipolar interaction and, depending on the spacer material and thickness, also interlayer exchange coupling (IEC). [40][41][42][43] As sketched in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Especially, vortices that are coupled vertically via a nonmagnetic interlayer are of interest, [23][24][25][26][27][28][29][30][31][32][33][34] as significant magnetoresistance and spin-torque phenomena may occur. [35][36][37][38][39] The relevant coupling mechanisms for such geometries are the magnetodipolar interaction and, depending on the spacer material and thickness, also interlayer exchange coupling (IEC). [40][41][42][43] As sketched in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The reports available on interlayer-coupled vortices can be categorized into static investigations 23,24,[26][27][28][29] on the one hand and magnetization dynamics studies using external fields [30][31][32][33][34] or spin-polarized currents [35][36][37][38][39] as excitation sources on the other hand. Many of the approaches used to analyze the system are theoretical, [30][31][32][33]39 whereas the experimental approaches are often based on integral resistance measurements, [35][36][37][38] or rely on information averaged from an ensemble of structures. [26][27][28][29] Only Refs.…”
Section: Introductionmentioning
confidence: 99%
“…4(d)]. Such a double-frequency mode has been observed in other STNOs [40][41][42][43][44][45][46], and can either result from the hopping between two frequencies, or from the simultaneous emission of two frequencies. Such cases are discussed in more detail in the following section.…”
Section: Frequency Domain Analysismentioning
confidence: 73%
“…By using the experimental values of M s 0 μ , d pl , α, and L, and by assuming a spin polarization of P ¼0.5 and a radius of the vortex core r 10 nm core = , we find a theoretical value for I / 4MHz/mA osc ω ∂ ∂ = in the low frequency regime, which matches with the observed slope experimentally of E 3.6 MHz/mA from Eq. (10). The jump in frequency can be calculated theoretically and accounts for a jump of 36 MHz similar to the observed one of E 37 MHz.…”
Section: Influence Of a V-av Pair In The Pl Onto The Oscillating Vortmentioning
confidence: 93%
“…Previous studies [10,11] have suggested that the two ferromagnetic layers of a nanocontacted spin-valve structure may contain a vortex state under certain conditions of the applied magnetic field and injected current. To date, a successful model to explain the new observed dynamics has been lacking.…”
Section: Introductionmentioning
confidence: 99%